Longitudinal control of blood pressure among a cohort of Ghanaians with hypertension: A multicenter, hospital‐based study. Issue 6 (30th April 2020) - Sarfo, Fred S.; Mobula, Linda; Plange‐Rhule, Jacob; Gebregziabher, Mulugeta; Ansong, Daniel; Sarfo‐Kantanka, Osei; Arthur, Lynda; Sablah, Jasper; Gavor, Edith; Burnham, Gilbert; Ofori‐Adjei, David
Abstract: There are limited data on factors associated with longitudinal control of blood pressure (BP) among Ghanaians on antihypertensive treatment. We sought to evaluate associations between prospective BP control and 24 putative factors within socio‐demographic, biological, and organizational domains. This is a cohort study involving 1867 (65%) adults with hypertension and 1006 (35%) with both hypertension and diabetes mellitus at five public hospitals. Clinic BP was measured every 2 months for 18 months of follow‐up. A multivariate logistic regression analysis was fitted via generalized linear mixed models to identify factors associated with clinic BP ≥ 140/90 mm Hg at each clinic visit during follow‐up. Mean age of study participants was 58.9 ± 16.6 years and 76.8% were females. Proportions with controlled BP increased from 46.3% at baseline to 59.8% at month 18, P  < .0001. Eight factors with adjusted OR (95% CI) associated prospectively with uncontrolled BP were male gender: 1.37 (1.09‐1.72), secondary education: 1.32 (1.00‐1.74), non‐adherence to antihypertensive treatment: 1.03 (1.00‐1.06), fruit intake: 0.94 (0.89‐1.00), duration of hypertension diagnosis: 1.01 (1.00‐1.02), hypertension with diabetes mellitus: 2.05 (1.72‐2.46), number of antihypertensive medications: 1.63 (1.49‐1.79), and estimated glomerular filtration rate (mL/min rise): 0.82 (0.76‐0.89). Interventions aimed at addressing modifiable factors associated with poorly controlled BP would be critical in prevention of cardiovascular diseases among Ghanaians.